Food Safety of Shrimp Paste Products in Sidoarjo Regency Judging from the Presence of Microbiological Contamination and Chemical Contamination - Aprilia, Dania Salshabilla; Rosida; Dany Priyanto, Anugerah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Shrimp paste is a processed fishery product made from shrimp, fish or both. Food safety is the conditions and efforts needed to prevent food from three possible contaminations, namely microbiological, chemical and other contamination that can disturb, harm and endanger human health. This research aimed to determine the relationship between hygiene and sanitation and microbiological contamination (Escherichia coli and Salmonella); and determine the presence of contamination (rhodamine B and lead) qualitatively and quantitatively in shrimp paste circulating in Sidoarjo Regency. This research was carried out by taking 23 samples from 23 traders in the centre of Sidoarjo Regency using the purposive sampling method. This research consisted of an interview process, sanitation hygiene observations, microbiological contamination analysis (Escherichia coli and Salmonella) and chemical contamination analysis (rhodamine B and lead). The results of microbiological analysis on 23 samples of shrimp paste in Sidoarjo Regency were positive for the presence of Escherichia coli bacteria. Two samples of shrimp paste had values ??< 3.6 MPN/g, and data was obtained that environmental sanitation practices correlated with Escherichia coli contamination in shrimp paste samples in Sidoarjo with (p<0.05). The presence of Salmonella bacteria and rhodamine B chemical contamination was not detected in all samples of shrimp paste in Sidoarjo Regency. However, 14 samples of shrimp paste were identified as contaminated with the heavy metal lead >1.0 mg/kg. Based on the results of these four parameters, the "I" shrimp paste sample has fulfilled the SNI (2716:2016) criteria well when compared with 22 other types of shrimp paste in Sidoarjo Regency.